2019
DOI: 10.1016/j.bja.2019.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic medicine in anaesthesiology: development and assessment of a curriculum in humanism for postgraduate anaesthesiology trainees

Abstract: Background: An unintended consequence of medical technologies is loss of personal interactions and humanism between patients and their healthcare providers, leading to depersonalisation of medicine. As humanism is not integrated as part of formal postgraduate anaesthesiology education curricula, our goal was to design, introduce, and evaluate a comprehensive humanism curriculum into anaesthesiology training. Methods: Subject-matter experts developed and delivered the humanism curriculum, which included interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Role play has been found to boost participants’ confidence in communication [ 44 , 118 , 142 , 144 ]. The use of the arts and humanities including poetry and literature [ 49 , 57 , 83 , 136 , 139 ], drawings and paintings [ 16 , 43 , 59 , 83 , 136 , 139 ], reflective writing [ 49 , 83 , 136 , 139 ], cultural studies and history [ 16 ], film [ 16 ], photography [ 59 ], and comics [ 5 ] have also shown to increase self-awareness and reflection [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Role play has been found to boost participants’ confidence in communication [ 44 , 118 , 142 , 144 ]. The use of the arts and humanities including poetry and literature [ 49 , 57 , 83 , 136 , 139 ], drawings and paintings [ 16 , 43 , 59 , 83 , 136 , 139 ], reflective writing [ 49 , 83 , 136 , 139 ], cultural studies and history [ 16 ], film [ 16 ], photography [ 59 ], and comics [ 5 ] have also shown to increase self-awareness and reflection [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…This quote epitomises empathy, which is perhaps, as Canales and colleagues 1 propose, an antidote to depersonalisation in healthcare and risk of physician burnout. Krasner and colleagues 3 have shown that increasing physician empathy (through well-being training) can reduce burnout.…”
mentioning
confidence: 87%
“…Canales and colleagues 1 have undertaken an important study because it tells us that humanism is important for high quality patient-centred care and for satisfaction by both patients and carers. The extent to which each element of their curriculum is important to this improvement remains to be tested, but we suggest revisiting the purpose and outcomes of the 'doctor as patient' exercise.…”
Section: Shifting the Focus From Empathy To Compassionmentioning
confidence: 99%
See 2 more Smart Citations